Self-assembling benzothiazole-based gelators: a mechanistic understanding of in vitro bioactivation and gelation - Citossi, Francesca; Smith, Thomas; Lee, Jong Bong; Segal, Joel; Gershkovich, Pavel; Stocks, Michael John; Bradshaw, Tracey D.; Kellam, Barrie; Marlow, Maria (American Chemical Society, 2018)
Low molecular weight gelators (LMWGs) of chemotherapeutic drugs represent a valid alternative to the existing poly-mer-based formulations used for targeted delivery of anticancer drugs. Herein we report the design and development of novel self-assembling gelators of the antitumour benzothiazole 5F 203 (1). Two different types of derivatives of 1 were synthesized, formed by an amide (2) and a carbamate (3a-3d) linker, respectively, which showed potent in vitro anti-tumour activity against MCF-7 mammary and IGROV-1 ovarian carcinoma cells. In contrast, MRC-5 fibroblasts were inherently resistant to the above derivatives (GI50>10 μM), thus revealing stark selectivity against the malignant cell lines over the non-transformed fibroblasts. Western blots assays demonstrated induction of CYP1A1 by 1 and its deriva-tives only in sensitive malignant cells (MCF-7), corroborating conservation of CYP1A1-mediated mechanism of action. The ability to form stable gels under relatively high strains was supported by rheological tests; in addition, their inner morphology was characterized as possessing a crossed-linked nanostructure, with formation of thick aggregates with variable widths between 1100 nm and 400 nm and lengths from 8 μm to 32 μm. Finally, in vitro dissolution studies proved the ability of hydrogel 2 to release 48% of 2 within 80 hours, therefore demonstrating its ability to act as a plat-form for localized delivery.